A functional mammalian target of rapamycin complex 1 signaling is indispensable for c‐Myc‐driven hepatocarcinogenesis. Issue 1 (22nd May 2017) - Liu, Pin; Ge, Mengmeng; Hu, Junjie; Li, Xiaolei; Che, Li; Sun, Kun; Cheng, Lili; Huang, Yuedong; Pilo, Maria G.; Cigliano, Antonio; Pes, Giovanni M.; Pascale, Rosa M.; et al.
Abstract : Amplification and/or activation of the c‐Myc proto‐oncogene is one of the leading genetic events along hepatocarcinogenesis. The oncogenic potential of c‐Myc has been proven experimentally by the finding that its overexpression in the mouse liver triggers tumor formation. However, the molecular mechanism whereby c‐Myc exerts its oncogenic activity in the liver remains poorly understood. Here, we demonstrate that the mammalian target of rapamycin complex 1 (mTORC1) cascade is activated and necessary for c‐Myc‐dependent hepatocarcinogenesis. Specifically, we found that ablation of Raptor, the unique member of mTORC1, strongly inhibits c‐Myc liver tumor formation. Also, the p70 ribosomal S6 kinase/ribosomal protein S6 and eukaryotic translation initiation factor 4E‐binding protein 1/eukaryotic translation initiation factor 4E signaling cascades downstream of mTORC1 are required for c‐Myc‐driven tumorigenesis. Intriguingly, microarray expression analysis revealed up‐regulation of multiple amino acid transporters, including solute carrier family 1 member A5 (SLC1A5) and SLC7A6, leading to robust uptake of amino acids, including glutamine, into c‐Myc tumor cells. Subsequent functional studies showed that amino acids are critical for activation of mTORC1 as their inhibition suppressed mTORC1 in c‐Myc tumor cells. In human hepatocellular carcinoma specimens, levels of c‐Myc directly correlate with those of mTORC1 activation as well as of SLC1A5 and SLC7A6. Conclusion : Our current study indicates that an intact mTORC1 axis is required for c‐Myc‐driven hepatocarcinogenesis; thus, targeting the mTOR pathway or amino acid transporters may be an effective and novel therapeutic option for the treatment of hepatocellular carcinoma with activated c‐Myc signaling. (Hepatology 2017;66:167–181).